Nisekoi, false love. Vol. 22: Bull's eye - Komi, Naoshi, 1986- (Viz Media, 2017)
Love triangle! Comedic antics!! Gang warfare?! It's hate at first sight when Raku Ichijo first meets Chitoge Kirisaki. But much to their chagrin, the two are forced into a false love relationship to keep the peace between their feuding gangster families. On Marika's wedding day, Raku bursts in just before the couple seal their vows. Will Raku and the gang manage to rescue Marika from her mother's minions? And when they return to their ordinary lives, how will the whole adventure affect Kosaki's and Chitoge's feelings for Raku?